Development and evaluation of a clinical research nursing module for undergraduate nursing schools: expanding Clinical Research Nurses' outreach. (March 2022) - Capili, Bernadette; Baker, Laura; Thangthaeng, Nopporn; Legor, Kristen; Larkin, Mary E; Jones, Carolynn T
Background: Clinical Research Nurses (CRNs) care for study participants and manage clinical research studies; yet the CRN practice role is rarely covered in undergraduate nursing curricula in the United States. Despite a burgeoning need for CRNs, the pipeline of clinical research nurse positions remains sparse. The International Association of Clinical Research Nurses's (IACRN) strategic goal to "engage with nursing schools to heighten awareness and inclusion of the CRN role competencies in nursing education" prompted the development of an educational lecture module to be disseminated to nursing schools. This project is a pilot launch of the module. Methods: A task force of IACRN was formed to develop educational materials that could be used as outreach to undergraduate nursing schools. The content included a slide presentation covering an overview of clinical research, the CRN practice, three embedded videos showing CRN and study participant perspectives, and coverage of the care of participants of research by staff nurses. Due to COVID-19 we revised our live lecture approach using either a live synchronous webinar presentation, or an embedded asynchronous course module with YouTube videos for course learning management systems. We presented the content to 408 nursing students attending three academic programs. To evaluate effectiveness and satisfaction, an anonymous, post-presentation survey using web-based Qualtrics XM was distributed to students. Results: Content and delivery of the module was positively evaluated. There was an improvement in knowledge in each topic. Evaluation responses showed that the content could likely or very likely improve care for their patients (87.4%) and improve patient education for patients in clinical trials (95%). Conclusions: Delivering a synchronous or asynchronous module about the CRN practice role to nursing students in academic nursing programs is valuable to increasing awareness of the care of patients in clinical trials, the CRN role, and future professional development.